(Ba+Co) codoped CdS thin films with enhanced magnetic and photodegradation properties. (13th February 2019) - Samiyammal, P; Parasuraman, K; Balu, A R
Abstract: Perfume atomizer is used to deposit undoped, Ba-doped (CdS:Ba), Co-doped (CdS:Co) and (Ba+Co) codoped CdS thin films. The structural, compositional, optical, electrical and magnetic properties were analyzed by XRD, SEM, EDX, XPS, UV–vis-NIR, two-point probe setup and VSM, respectively. The undoped, Ba-doped, Co-doped and (Ba+Co) codoped CdS thin films crystallize in hexagonal structure with crystal grains growing predominantly along the (0 0 2) plane. EDX and XPS spectrum confirmed the existence of Cd, S, Ba and Co in the (Ba+Co) codoped CdS thin film. Decreased resistivity was observed for the Ba-doped, Co-doped and (Ba+Co) codoped CdS thin films. The codoped film exhibits improved ferromagnetic property with the presence of well-defined hysteresis loop. Degradation efficiencies of 79.25%, 80.19% and 85.42% was observed for the CdS:Ba, CdS:Co and (Ba+Co) codoped CdS thin films which seems to be better than that of the undoped CdS (70.59%) thin film against metanil yellow under the exposure of visible light.